The protective effect of kaempferol on high glucose-stimulated renal tubular epithelial cells - Xiao-Cui Jiao; Ying Li; Di Wu; Xue-Guang Zhang; Fei Hou (BMC Nephrology)
Abstract Background The oxidative stress and apoptosis of renal tubular epithelial play an important role in the progression of diabetic nephropathy. Blocking oxidative stress and apoptosis of renal tubular epithelial could be a novel therapeutic target for diabetic nephropathy. Kaempferol (KMP), a natural phytoestrogen and common dietary flavonoid, has various biological effects including anti-oxidation, anti-apoptosis and anti-inflammation. KMP has protective effect against oxidative stress-related diseases, such as ischemia-reperfusion induced myocardium injuries, osteoporosis, obesity and so on. In our research, we observed the influence of KMP on high glucose (HG) cultured HK-2 cells and explored its mechanisms from the aspect of oxidative stress and apoptosis. Methods To find out the safety and effective concentration of KMP in our experiment, cell viability under different concentrations was detected using the MTS method. The protein and mRNA expression of SOD2 and catalase were detected by Western blot and Real-time PCR; the protein expression of Sirt3, Bax, Bcl-2, cleaved-caspase3, Akt, p-Akt, FoxO3a, p- FoxO3a were detected by Western blot; the ROS level in cellular was detected by cell flow cytometer. Results We found that HK-2 cells stimulated with both 10µM KMP and HG exhibited higher viability compared to those stimulated by HG only. Incubation with KMP could reverse the undesirable effects of HG on SOD2, catalase, cleaved caspase-3, Bax/Bcl-2 ratio and the generation of ROS. Furthermore, Western blot and Real-time PCR results showed that the expression levels of Sirt3, p-Akt/Akt ratio and p-FoxO3a/FoxO3a ratio were markedly increased in the KMP plus HG group compared to the HG group. Furthermore, downregulating Sirt3 expression in HK2 cells impairs the protective effect of KMP, leading to a reduction in HK2 cell viability and an elevation in ROS levels. Conclusion In summary, KMP could alleviate HG-induced oxidative stress and apoptosis, and its cytoprotection is associated with Sirt3 expression and the activation of ROS-sensitive Akt/FoxO3a signaling pathway.